Poverty and the Poor in the Media Discourse in Poland: Compassion or Blame? - Pokrzywa, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The purpose of this article is to show how poverty and the people who experience it are presented by various media (press, television programmes, etc.) in Poland. Referring to research and media analyses of the representation of this phenomenon, attempts were made to reveal the causes and valuations attributed to it. The media discourse on poverty shapes and proliferates social perceptions about it. It is crucial because it influences how fellow citizens treat the poor and policies aimed at minimising this phenomenon. Two dominant mass media narratives about those affected by poverty can be divided as follows: 1) the deserving poor worthy of support because their poverty is due to external sources beyond their power, and 2) the undeserving poor, who are themselves responsible for their material situation due to bad attitudes, habits, and deviant behaviours.